Environmental evolution, faunal and human occupation since 2 Ma in the Anagni basin, central Italy - Fabio Florindo (Nature Portfolio, 2021)
Abstract We present the study of a composite, yet continuous sedimentary succession covering the time interval spanning 2.6–0.36 Ma in the intramontane basin of Anagni (central Italy) through a dedicated borecore, field surveys, and the review of previous data at the three palaeontological and archaeological sites of Colle Marino, Coste San Giacomo and Fontana Ranuccio. By combining the magneto- and chronostratigraphic data with sedimentologic and biostratigraphic analysis, we describe the palaeogeographic and tectonic evolution of this region during this entire interval. In this time frame, starting from 0.8 Ma, the progressive shallowing and temporary emersion of the large lacustrine basins and alluvial plains created favorable conditions for early hominin occupation of the area, as attested by abundant tool industry occurrences and fossils. This study provides new constraints to better interpret the hominin migratory dynamics and the factors that influenced the location and spatial distribution during the early occupation of this region.